Are joints affected by gout also affected by osteoarthritis?. Issue 10 (6th February 2007) - Roddy, Edward; Zhang, Weiya; Doherty, Michael
Abstract : Objectives: To determine whether joints affected by gout are also affected by osteoarthritis (OA). Methods: A postal questionnaire was sent to all adults aged over 30 years registered with two general practices. The questionnaire assessed a history of gout (doctor diagnosed, or episodes suggestive of acute crystal synovitis) and medication use. Patients who possibly had gout attended for clinical assessment to verify the diagnosis on clinical grounds and assess the distribution of joints affected by acute attacks of gout and OA. Adjusted odds ratios (aOR) and 95% confidence intervals (CI) were calculated between the history of an acute attack of gout and the presence of OA at an individual joint adjusted for age, gender, body mass index and prior diuretic use in a binary logistic regression model. Results: A total of 4249 completed questionnaires were returned (32%). From 359 attendees, 164 cases of gout were clinically confirmed. A highly significant association existed between the site of acute attacks of gout and the presence of OA (aOR 7.94; 95% CI 6.27, 10.05). Analysis at individual joint sites revealed a significant association at the first metatarsophalangeal joint (aOR 2.06; 95% CI 1.28, 3.30), mid-foot (aOR 2.85; 95% CI 1.34, 6.03), knee (aOR 3.07; 95% CI 1.05, 8.96) and distal interphalangeal joints (aOR 12.67; 95% CI 1.46, 109.91). Conclusion: Acute attacks of gout at individual joint sites are associated with the presence of clinically assessed OA at that joint suggesting that OA may predispose to the localised deposition of monosodium urate crystals.